Association of intercellular adhesion molecule 1 polymorphisms with retinopathy in Chinese patients with Type 2 diabetes - Liu, L.; Yu, Q.; Wang, H.; Zhang, S. X.; Huang, C.; Chen, X. (Diabetic medicine, 2006)
Aims  To investigate the relationship of the K469E and G241R polymorphisms of the intercellular adhesion molecule 1 (ICAM‐1) gene with diabetic retinopathy in Chinese patients with Type 2 diabetes mellitus. Patients and methods  One hundred and seventy‐two Chinese patients with Type 2 diabetes and 80 normal control subjects were recruited. Patients with diabetes were placed into two groups: the diabetic retinopathy (DR) group and the non‐diabetic retinopathy (NDR) group. The DR group was subdivided into those with proliferative retinopathy (PDR) and non‐proliferative retinopathy (NPDR). Genomic DNA was prepared using the hydroxybenzene–chloroform extraction method. Genotypes and alleles were detected by polymerase chain reaction–heteroduplex–single‐strand conformation polymorphism (PCR–HA–SSCP) analysis combined with gene sequencing. Results  The patients with retinopathy had an increased frequency of the K469K genotype compared with both the patients without retinopathy and the control subjects (61.4 vs. 40.0 and 35.0%, respectively; χ2 = 8.280 and 13.952, respectively; P < 0.05). The frequency of the K allele in the DR group was higher than in the NDR group and control subjects (75.4 vs. 58.8 and 61.3%, respectively; χ2 = 9.693 and 11.219, respectively; P < 0.05). Genotype and allele frequencies were similar in the NDR group and control subjects, and in the PDR and NPDR groups. Conclusion  The ICAM‐1 gene K469E polymorphism is associated with diabetic retinopathy in Chinese patients with Type 2 diabetes. Patients with the K469K genotype were more likely to have diabetic retinopathy than patients with the K469E or E469E genotype. Diabet. Med. 23, 643 –648 (2006)